Developing Administrative Excellence for Enhanced Educational Service Quality in Islamic Secondary Schools - Hasan, Moch. Sya'roni; Azizah, Mar’atul; Ainiyah, Qurrotul; Solechan, Solechan; Sunardi, Sunardi; Budiyono, Ahmad; Mastor, Humairourrohmah binti (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2025)
This research aims to analyse the competency development process of administrative staff at MTs Negeri 1 Jombang and its implications for improving the quality of educational services. Using a qualitative approach with a case study design, this research involved in-depth interviews with madrasah principals, administrative staff, and educators, as well as participatory observation and documentation studies. Data analysis was conducted interactively using the Miles and Huberman model. The research findings indicate that administrative staff competency development is implemented structurally through four competency standards: personality, social, technical, and managerial. Development strategies include routine training programs, competency-based performance evaluations, continuous supervision, and implementation of digital service systems through One-Stop Integrated Services (PTSP). Despite challenges, particularly technology literacy gaps among staff, collaborative solutions through internal mentoring and adaptive training have proven effective in significantly enhancing administrative capacity. This research affirms that administrative staff are no longer merely support personnel, but essential actors in the success of madrasah management. Theoretically, this research extends the application of competency-based management and learning organisation models by positioning administrative staff as key subjects. In practice, these findings encourage madrasahs and similar educational institutions to design training programs that are better aligned with the real needs of administrative staff. Furthermore, this study makes a unique contribution to filling the literature gap on madrasah administrative management by providing an integrative model that connects digital transformation, competency-based development, and service quality improvement.